Identifikasi Bakteri Gram Positif Pada Saliva Penderita Diabetes Melitus Tipe 2 Di Puskesmas Simalingkar - Gultom, Atri Gustiana; Pohan, Yuyun Angraini (Program Studi S1 Farmasi, STIKES Senior, Medan, 2024)
Hyperglycemia is a decrease in insulin secretion by pancreatic beta cells or impaired insulin function (insulin resistance) is a sign of a metabolic disease known as type 2 diabetes mellitus. This study used a descriptive method by collecting saliva samples from 25 type 2 diabetes patients who were regularly examined at the Simalingkar Community Health Center. This study aims to identify Gram-positive bacteria in the saliva of type 2 diabetes mellitus sufferers at the Simalingkar Community Health Center or using Gram staining and bacterial identification through Blood Agar Plate (BAP) culture and biochemical tests (catalase test). Gram staining results showed that 10 of the 25 samples (40%) contained Gram positive bacteria, with details of 1 Streptococcus isolate (4%), 3 Staphylococcus isolates (12%), and 6 Bacillus subtilis isolates (24%). A total of 15 samples (60%) contained Gram negative bacteria. Microscopic identification showed that Gram-positive cocci bacteria included 3 isolates of Staphylococcus aureus and 1 isolate of Streptococcus mutans, while Gram-positive rod bacteria included 6 isolates of Bacillus subtilis. For Gram-negative bacteria, 3 isolates were found in the form of cocci and 12 isolates in the form of rods. Biochemical tests showed that Staphylococcus aureus was catalase positive with foam results, while Streptococcus mutans was catalase negative without foam formation. This study shows a significant prevalence of Gram-positive bacteria in the saliva of type 2 diabetes mellitus sufferers, which is likely caused by hyperglycemia conditions that support the growth of pathogenic bacteria. These results provide important insights into the relationship between type 2 diabetes mellitus and changes in oral flora, as well as the need for more intensive oral health care in people with diabetes.